2016
DOI: 10.1002/hed.24300
|View full text |Cite
|
Sign up to set email alerts
|

Narrow band imaging for the diagnosis of head and neck squamous cell carcinoma: A systematic review

Abstract: Narrow band imaging (NBI) is reported to improve the diagnostic accuracy of head and neck cancers. The purpose of this review was to evaluate the diagnostic accuracy of NBI in the literature. A systematic review was performed in PubMed, Web of Knowledge, and the Cochrane Library until March 2015. Two reviewers independently assessed articles and extracted data. Meta-analyses were performed in MetaDisc 1.6. Five hundred seventeen studies were identified and 17 were included in this study. Combined use of NBI an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 70 publications
1
88
0
Order By: Relevance
“…25 Cross-sectional imaging of the neck using contrast-enhanced CT or MRI has a limited diagnostic yield ranging between 9.3% and 23%, but reaches 73% with MRI 3D T1-weighted high-resolution isotropic volume sequences. If FNAC or core biopsy confirms the diagnosis of SCCUP, standard flexible endoscopic examination should be supplemented with biologic endoscopy.…”
Section: Diagnostic Approachmentioning
confidence: 99%
“…25 Cross-sectional imaging of the neck using contrast-enhanced CT or MRI has a limited diagnostic yield ranging between 9.3% and 23%, but reaches 73% with MRI 3D T1-weighted high-resolution isotropic volume sequences. If FNAC or core biopsy confirms the diagnosis of SCCUP, standard flexible endoscopic examination should be supplemented with biologic endoscopy.…”
Section: Diagnostic Approachmentioning
confidence: 99%
“…Furthermore, a small number of studies also evaluated its impact in the detection of head and neck SCCUP. In a recent review, Cosway et al found a remarkable sensitivity (74%) and specificity (86%) of NBI in the SCCUP scenario, underlining its potential in identifying patients even with tiny and superficial mucosal lesions. What is more striking is that NBI demonstrated a high negative predictive value, providing good evidence that patients with a negative evaluation have a very low probability of having UADT primary lesions .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review, Cosway et al found a remarkable sensitivity (74%) and specificity (86%) of NBI in the SCCUP scenario, underlining its potential in identifying patients even with tiny and superficial mucosal lesions. What is more striking is that NBI demonstrated a high negative predictive value, providing good evidence that patients with a negative evaluation have a very low probability of having UADT primary lesions . The sensitivity, specificity, and positive and negative predictive values of NBI in SCCUP recently reported in the literature are summarized in Table .…”
Section: Discussionmentioning
confidence: 99%
“…One of the limitations in most of the studies assessing accuracy of NBI is lack of follow‐up data, which could explain high NPV achieved in previous studies . We also included a high number of patients with no biopsies taken (75.2%) at initial visit.…”
Section: Discussionmentioning
confidence: 99%